CO2 concentration from turbocharged common rail diesel engine dually fueled with compressed biomethane gas controlled at optimum ratio - Niti Kammuang-Lue (2018)
© The Authors, published by EDP Sciences, 2018. The objectives of this study are to investigate the carbon dioxide (CO2) concentration from the compressed biomethane gas (CBG) and diesel dual-fueled diesel engine and to compare the CO2 concentration produced from the dual-fueled and the diesel-fueled engines. The duration of CBG injection was controlled by following the optimum ratio of the CBG obtained from the previous study. During the test, the engine speed was varied from 1,000 to 4,000 rpm and the engine torque was maintained to be 25, 50, 75 and 100% of the maximum engine torque. Experiment was divided into two parts consisting of the dual-fueled and the diesel-fueled modes. From the dual-fueled mode, when the engine speed increased, the CO2 concentration decreased. Because the optimum ratio of the CBG and the volumetric efficiency decrease during the high engine speed range, the proportion of the diesel increases, the incomplete combustion occurs. The unburned carbon oxidizes to be the CO in higher proportion than the CO2, thus, the CO2 consequently decreases. From the CO2 comparison, the dual-fuel mode produced the CO2 nearly the same as that of the diesel-fuel mode during the low engine torque. On contrary, the dual-fuel mode had higher CO2 concentration during the high engine torque.